2006
DOI: 10.1007/s00296-006-0128-1
|View full text |Cite
|
Sign up to set email alerts
|

Flexible flatfoot and related factors in primary school children: a report of a screening study

Abstract: The aim of this study was to analyze the longitudinal arch morphology and related factors in primary school children. Five hundred and seventy-nine primary school children were enrolled in the study. Generalized joint laxity, foot progression angle, frontal hindfoot alignment, and longitudinal arch height in dynamic position were evaluated. The footprints were recorded by Harris and Beath footprint mat and arch index of Staheli was calculated. The mean age was 9.23 +/- 1.66 years. Four hundred and fifty-six ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
3
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 18 publications
4
76
3
11
Order By: Relevance
“…The percentage distribution of flatfeet was higher in boys than girls. Our results confirms the findings of Chen et al (2009);Chang et al (2010); (2014); El et al (2006); Gracia et al (1999).…”
Section: Discussionsupporting
confidence: 83%
“…The percentage distribution of flatfeet was higher in boys than girls. Our results confirms the findings of Chen et al (2009);Chang et al (2010); (2014); El et al (2006); Gracia et al (1999).…”
Section: Discussionsupporting
confidence: 83%
“…Various studies have suggested a definition based on footprints, [1][2][3][4] heel-to-arch width ratio, 5 subjective assessment, 6,7 or radiographic measurements. [8][9][10] Classically, the diagnosis of flatfoot is assigned to patients who appear to have a collapsed medial arch, yet this is a subjective measure that neglects etiology or specific anatomic considerations.…”
Section: Doi: 101542/peds2015-1230mentioning
confidence: 99%
“…Los problemas ortopédicos del pie en el niño son los más frecuentes en esta época de la vida. Por este motivo es importante hacer la diferenciación entre un pie normal y un pie alterado que necesita tratamiento del especialista en forma precoz (El et al, 2006;Vasconcellos et al, 2011).…”
Section: Introductionunclassified
“…Los problemas ortopédicos del pie en el niño son los más frecuentes en esta época de la vida. Por este motivo es importante hacer la diferenciación entre un pie normal y un pie alterado que necesita tratamiento del especialista en forma precoz (El et al, 2006;Vasconcellos et al, 2011).Facultad de Ciencias, Departamento de Biología, Universidad de Tarapacá, Arica, Chile. Esta investigación fue financiada por la Universidad de Tarapacá a través del Proyecto Mayor Nº 5710-12.…”
unclassified